2016
DOI: 10.1016/j.jss.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate timing of blood sampling for blood gas analysis in the ventilated rabbit

Abstract: In ventilated rabbits, arterial PO and SO stabilized in 0.5 min. No venous value stabilized after the RR change. Only the PCO and pH of venous samples may be an alternative to arterial samples under the defined formula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The low level of partial pressure of oxygen (PO2) and subsequent high level of and partial pressure of carbon dioxide (PCO2) in the blood can occur due to the decline in gases exchange resulting from inflammation and obstruction of the airways which causes the hypoventilation and dyspnea. If the low level of PO2 (hypoxia) is prolonged, it can cause contraction of the blood vessels in the lungs and the pulmonary hypertension [84]. The researchers found that the cell therapy with the MSCs has been able to improve the blood PO2 level through the mediators and inflammation reduction.…”
Section: The Effects Of Msc Therapy On Blood Gases Situationmentioning
confidence: 99%
“…The low level of partial pressure of oxygen (PO2) and subsequent high level of and partial pressure of carbon dioxide (PCO2) in the blood can occur due to the decline in gases exchange resulting from inflammation and obstruction of the airways which causes the hypoventilation and dyspnea. If the low level of PO2 (hypoxia) is prolonged, it can cause contraction of the blood vessels in the lungs and the pulmonary hypertension [84]. The researchers found that the cell therapy with the MSCs has been able to improve the blood PO2 level through the mediators and inflammation reduction.…”
Section: The Effects Of Msc Therapy On Blood Gases Situationmentioning
confidence: 99%
“…The results of the analysis of blood gases have an important role in the diagnosis and management of pulmonary capacity, the status of oxygenation and the balance of acid and base. Low levels of oxygen and high levels of carbon dioxide in the blood can occur due to decreasing gas exchange, which results from severe in ammation and obstruction of airway 28 . This condition occurred after the onset of in ammation in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The patient usually breathes the hypoxic gas mixture for 20 min, or until SpO 2 reaches 85%. Although this is shorter than the briefest commercial flight, oxygenation equilibrium is usually reached within this time 134 157. The patient is advised to have in-flight oxygen if PaO 2 falls below 6.6 kPa (<50 mm Hg) or SpO 2 remains <85%1 17 (see page 11).…”
Section: Methodsmentioning
confidence: 99%